2022
DOI: 10.3390/antibiotics11070888
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Susceptibility and Resistance Genes in Oral Clinical Isolates of Prevotella intermedia, Prevotella nigrescens, and Prevotella melaninogenica

Abstract: The Prevotella genus is a normal constituent of the oral microbiota, and is commonly isolated from mechanically treated polymicrobial infections. However, antibiotic treatment is necessary for some patients. This study compared the antibiotic susceptibility and the presence of resistance genes in clinical oral isolates of P. intermedia, P. nigrescens, and P. melaninogenica. Antibiotic susceptibility was assessed using the agar dilution method. PCR confirmed the species and resistance gene frequency in the Prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 30 publications
3
6
0
Order By: Relevance
“…Although more often associated with abdominal infections (appendicitis, cholangitis, or diverticulitis), some authors recommended an appropriate evaluation of a possible abdominal or perineal source of infection in case of meningitis caused by Streptococcus anginosus [ 17 ]. In immunocompromised patients, this is frequently associated with other Gram-negative or anaerobic pathogens [ 18 ], as we have noted in our patient. In line with many other reports, the streptococcal bacteria isolated in CSF were susceptible to penicillin [ 19 ].…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Although more often associated with abdominal infections (appendicitis, cholangitis, or diverticulitis), some authors recommended an appropriate evaluation of a possible abdominal or perineal source of infection in case of meningitis caused by Streptococcus anginosus [ 17 ]. In immunocompromised patients, this is frequently associated with other Gram-negative or anaerobic pathogens [ 18 ], as we have noted in our patient. In line with many other reports, the streptococcal bacteria isolated in CSF were susceptible to penicillin [ 19 ].…”
Section: Discussionsupporting
confidence: 77%
“…The strain of Prevotella involved in our case was not identified; it was sensitive to most beta–lactam antibiotics, except penicillin. Of the three most common Prevotella strains ( P. intermedia , P. melaninogenica , and P. nigrescens ), only P. intermedia was identified as susceptible to aminopenicillins, as in our case [ 18 ].…”
Section: Discussionmentioning
confidence: 69%
“…Castillo et al previously reported on the antibiotic susceptibility and presence of resistance genes in clinical oral isolates of Prevotella intermedia. They found the frequency of resistance gene in Prevotella intermedia (species) to be 30.2% [ 34 ]. Furthermore, Prevotella intermedia was resistant to metronidazole at a frequency of 30%; however, no isolates of Prevotella intermedia were resistant to amoxicillin/clavulanic acid, tetracycline, or clindamycin [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…They found the frequency of resistance gene in Prevotella intermedia (species) to be 30.2% [ 34 ]. Furthermore, Prevotella intermedia was resistant to metronidazole at a frequency of 30%; however, no isolates of Prevotella intermedia were resistant to amoxicillin/clavulanic acid, tetracycline, or clindamycin [ 34 ]. Notably, Prevotella intermedia ZT belongs to a genus marked with highly dynamic genomes.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, more than 50% Prevotella species isolated from the clinical samples were beta lactamase-producing organisms with 17.1 to 26.3% resistance to amoxicillin; fortunately, these species were susceptible to amoxicillin-clavulanic acid [ 49 ]. Among the three Prevotella species studied for their antimicrobial resistance to first- and second-line antibiotics in PD treatment, in an in vitro study, a key aspect of the findings revealed that P. nigrescens had the highest amoxicillin, amoxicillin clavulanic acid and clindamycin [ 50 ]. In a recent retrospective study by Jepsen et al, 2021, an exponential increase in the resistance to selected antibiotics with associated with a statistically significant decline in susceptibility to prescribed antibiotics was observed [ 51 ].…”
Section: Treatment Options Available For Treating Bacterial Infection...mentioning
confidence: 99%